DYNAMICS OF RAINFALL AND TEMPERATURE IN NORTH SUMATRA PROVINCE: COMPREHENSIVE ANALYSIS OF TEMPORAL TRENDS - Lubis, Riri Syafitri; Suzana, Yenny; Syarah, Fatmah; Fajriana, Fajriana; Rozi, Fachrur; Nusantara, Badai Charamsar (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
This research aims to analyze the temporal trends of rainfall and temperature in North Sumatra Province, focusing on the Medan and Deli Serdang regions. The data used in this study was obtained from the Central Statistics Agency of North Sumatra (BPS Sumut) and spans the period from January 2000 to December 2022. The Mann-Kendall test was applied to identify trends, Sen's Slope Estimator measured the trend slope, and Pearson correlation analysis assessed the relationship between rainfall and temperature. Key findings indicate that Medan has a higher monthly rainfall average than Deli Serdang, with both regions showing a significant increasing trend in rainfall, although the rise is gradual. Additionally, a positive trend in temperature was identified, reflecting broader climate change patterns. However, the correlation between rainfall and temperature was weak, indicating minimal direct interaction between these variables in the study areas. These results contribute valuable insights into climate dynamics and are critical for the development of climate change adaptation strategies in North Sumatra Province.